Wymiana wartości niematerialnych w mediach społecznościowych - Krzysztof Kubiak (Ekonomiczne Problemy Usług, 2015)
Turbulence and dynamics of the external environment is a prerequisite to update knowledge and implement social media. This type of media is characterized by interactive communication between participants in order to meet the needs of personal and social nature. This article aims to identify the factors affecting the process of values exchange in social media. These factors are defined with a use of methodology of network thinking. It allows you to look at the problem from different perspectives and determine the strength and nature of the relationship between individual elements of the network. The study was conducted among young respondents aged between 14 and 18 years and research workers. An additional purpose of this article is to test the research tool and so the results of the study should not be generalized to the entire population of respondents.